Early vedolizumab trough levels predict combined endoscopic and clinical remission in inflammatory bowel disease. Issue 6 (1st July 2019) - Hanžel, Jurij; Sever, Nejc; Ferkolj, Ivan; Štabuc, Borut; Smrekar, Nataša; Kurent, Tina; Koželj, Matic; Novak, Gregor; Compernolle, Griet; Tops, Sophie; Gils, Ann; Drobne, David
Abstract : Background: The relationship between vedolizumab trough levels and combined endoscopic and clinical remission is unknown. Objective: To compare vedolizumab trough levels in patients with and without combined remission within the first year of treatment. Methods: We prospectively collected vedolizumab trough levels in 51 consecutive patients (28 Crohn's disease (CD) and 23 ulcerative colitis (UC)) before all infusions up to week 22, and at weeks 38 and 54, with concentrations measured after study completion. Centrally read endoscopy was performed at a median of 46 weeks. The primary outcome was combined endoscopic (CD: Simple endoscopic score for CD (SES‐CD) < 4 without ulceration; UC: Mayo endoscopic subscore ≤ 1) and clinical remission (CD: resolution of abdominal pain; UC: resolution of rectal bleeding; both: resolution of altered bowel habit). Results: Median vedolizumab trough levels at weeks 6 (25.7 vs 15.6 µg/mL; P = 0.015) and 22 (15.1 vs 4.9 µg/mL; P = 0.001) were higher in patients with combined remission. A threshold of 22 µg/mL at week 6 (area under the curve (AUC) 0.733; 95% confidence interval 0.567–0.899) and 8 µg/mL at week 22 (AUC 0.819; 95% confidence interval 0.692–0.946) predicted combined remission. Conclusion: Early vedolizumab trough levels predicted combined endoscopic and clinical remission highlighting their possible use in clinical practice.